South Yorkshire Cohort: a 'cohort trials facility' study of health and weight - Protocol for the recruitment phase - Copeland Rob; Tod Angela; Nicholl Jon; Cooper Cindy L; Blackburn Joanna; Smith Christine; Bissell Paul; Relton Clare; Loban Amanda; Chater Tim; Thomas Kate; Young Tracy; et al. (BMC, 2011)
Abstract Background Growing levels of both obesity and chronic disease in the general population pose a major public health problem. In the UK, an innovative 'health and weight' cohort trials facility, the 'South Yorkshire Cohort', is being built in order to provide robust evidence to inform policy, commissioning and clinical decisions in this field. This protocol reports the design of the facility and outlines the recruitment phase methods. Method/Design The South Yorkshire Cohort health and weight study uses the cohort multiple randomised controlled trial design. This design recruits a large observational cohort of patients with the condition(s) of interest which then provides a facility for multiple randomised controlled trials (with large representative samples of participants, long term outcomes as standard, increased comparability between each trial conducted within the cohort and increased efficiency particularly for trials of expensive interventions) as well as ongoing information as to the natural history of the condition and treatment as usual. This study aims to recruit 20,000 participants to the population based South Yorkshire Cohort health and weight research trials facility. Participants are recruited by invitation letters from their General Practitioners. Data is collected using postal and/or online patient self completed Health Questionnaires. NHS numbers will be used to facilitate record linkage and access to routine data. Participants are eligible if they are: aged 16 - 85 years, registered with one of 40 practices in South Yorkshire, provide consent for further contact from the researchers and to have their information used to look at the benefit of health treatments. The first wave of data is being collected during 2010/12 and further waves are planned at 2 - 5 year intervals for the planned 20 year duration of the facility. Discussion The South Yorkshire Cohort combines the strengths of the standard observational, longitudinal cohort study design with a population based cohort facility for multiple randomised controlled trials in a range of long term health and weight related conditions (including obesity). This infrastructure will allow the rapid and cheap identification and recruitment of patients, and facilitate the provision of robust evidence to inform the management and self-management of health and weight.